2014
DOI: 10.1002/ejoc.201403301
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed α‐Arylation Reactions in Total Synthesis

Abstract: The development of palladium‐catalyzed α‐arylation of carbonyl compounds has emerged as a new avenue in the design of new routes for the synthesis of natural products and active pharmaceutical ingredients (APIs). In many cases, syntheses based on α‐arylation strategies provide elegant routes in terms of increasing the overall yields, improving the synthesis scope, and decreasing the number of steps. This microreview aims to highlight the importance of palladium‐catalyzed α‐arylation methodologies, covering a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 130 publications
(68 reference statements)
1
27
0
1
Order By: Relevance
“…NMR spectra were obtained at the Servei de Recursos Científics i Tècnics (SRCT), URV, with Varian (Agilent) Mercury VX400 or NMR System400 400 MHz spectrometers and calibrated to residual solvent peaks. Chemical and shifts for 1 H and 13 C{ 1 H} NMR spectra are reported relative to TMS. ICP analyses were conducted at the SCRT using an ICP-OES Spectro Arcos instrument.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectra were obtained at the Servei de Recursos Científics i Tècnics (SRCT), URV, with Varian (Agilent) Mercury VX400 or NMR System400 400 MHz spectrometers and calibrated to residual solvent peaks. Chemical and shifts for 1 H and 13 C{ 1 H} NMR spectra are reported relative to TMS. ICP analyses were conducted at the SCRT using an ICP-OES Spectro Arcos instrument.…”
Section: General Considerationsmentioning
confidence: 99%
“…[1][2][3][4][5][6] These coupling processes had a transformative impact on chemicals industries and have been employed in a number of industrial applications [7,8] as well as reported in numerous publications on the syntheses of complex organic molecules and materials, such as natural products, fine chemicals, drugs, agrochemicals and polymers. [9][10][11][12][13] In most cases, the new reaction development was performed under conventional batch synthesis conditions, whereas most chemical companies, especially in the pharmaceutical and speciality chemicals fields, are rapidly developing capability in continuous flow manufacturing. [14,15] The use of Pd-based catalysts under flow conditions represents specific challenges of production of solids and leaching of Pd into the products, which complicate the development of generic, efficient manufacturing protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Colacot, der in dieser Rubrik vorgestellt wurde, als ihm der Applied Catalysis Award der RSC verliehen worden war,3a hat außerdem den Award in Industrial Chemistry der ACS für 2015 erhalten und wird 2016 Empfänger der Medaille der indischen chemischen Forschungsgemeinschaft (CRSI) sein. Er hat kürzlich im European Journal of Organic Chemistry einen Microreview über palladiumkatalysierte α‐Arylierungen veröffentlicht 3b …”
Section: Ausgezeichnet …︁unclassified
“…Molecular building blocks possessing discrete conjugated segments that can be combined with other conjugated molecular units in a facile manner are widely utilized in pharmaceuticals 1 and organic electronics. 2 Moieties such as diketopyrrolopyrrole 1 and isoindigo 2 are widely used in the latter field for the synthesis of conjugated small molecules and polymers.…”
Section: Introductionmentioning
confidence: 99%